KINSHIP PRACTICE OF TOBA BATAK MOSLEM AS A LAND CONTROL STRATEGY IN ASAHAN - Ritonga, Sakti; Abdoellah, Oekan S. (UIN Sumatera Utara, 2020)
Abstract: This study shows the use of Toba Batak Moslem kinship relations as a livelihood strategy for land control in the changing space of power since the Malay-Islamic era in Asahan through the perspective of Bourdieu's theory of practice. The research was conducted using ethnographic methods. The analysis units are determined in stages starting from the family, descent group, clan association, and the Toba Batak community in the hinterland areas of Bandar Pulau, Bandar Pasir Mandoge and Buntu Pane. The results of the study found that adaptation strategies have expanded alliances and increased the practical function of the Toba Batak kinship in an effort to control land as the most important source of livelihood as a corporate kinship unit. Contestation of land is getting more complicated as the influence of plantation corporate capital and state power enters the village. When dealing with the interests of other larger institutions such as plantation companies and the state in terms of land disputes, it appears that the use of clan networks or descent groups is limited in function, when compared with the competition for resources among Toba Batak families. Keywords: kinship practices, livelihood strategies, migration, Toba Batak Moslem